DISTRIBUTED BUSINESS INTELLIGENCE A NEW APPROACH IN ECONOMICAL EDUCATION - Banica, Logica; Pirvu, Daniela; Stefan, Cristian (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The focus area of this paper is twofold: covering the theoretical background about cloud-based Business Intelligence, and the practical approach using the Jaspersoft environment. Also, by choosing the main application area, we emphasized the advantage of using such instruments as an educational tool, with the goal of giving the students an opportunity to discover data collections and explore analysis methods. After an overview of the Business Intelligence and Cloud Computing main concepts, we have pointed out the benefits of using BI in the Software as a Service (SaaS) philosophy, and we used the facilities of Jaspersoft BI software to model frequently used analysis requirements on several virtual firms